PELATIHAN PENULISAN KARYA SASTRA DAN KARYA TULIS ILMIAH UNTUK MENINGKATKAN KOMPETENSI SISWA SMP NEGERI 149 JAKARTA TIMUR - Redjeki Agoestyowati; Nurul Giswi Karomah (JURNAL ABDIMAS PLJ, 2024)
This community service discusses writing scientific papers or literary works. Writing literary works and scientific papers is a writing process based on scientific principles. This principle is an important foundation for ensuring the validity and accuracy of the work produced. The scientific writing training aims to foster interest and creative and innovative spirit from students at SMP 149 East Jakarta so that they can produce scientific works in accordance with the correct writing rules. In addition, this training also aims to improve students' critical, creative, communicative, and collaborative thinking skills. The evaluation of this training activity showed satisfactory results with full support from the school and active participation from all participants. It is hoped that this kind of activity can continue and involve the role of accompanying teachers.